Electrical characterization of Si/InN nanowire heterojunctions. (6th December 2017) - Alagha, S; Zhao, S; Mi, Z; Watkins, S P; Kavanagh, K L
Abstract: We report on the electrical properties of undoped, Si-doped and Mg-doped InN nanowires measured directly on degenerate n-type and p-type Si substrates. The transport was measured with a nanoprobe technique inside a scanning electron microscope. The resulting average current density versus voltage characteristics are weakly rectifying for InN grown on n + –Si with similar ratios for all InN dopant types. On p + –Si, Mg-doped InN nanowires show a strong rectification behavior with opposite voltage polarity compared to n + –Si, while undoped and Si-doped nanowires show nearly symmetric transport. These characteristics are analyzed in terms of the properties of broken gap band offsets at the Si/InN heterojunction.